Defining the expression pattern of the LGI1 gene in BAC transgenic mice - Head, Karen; Gong, Shiaoching; Joseph, Sheldon; Wang, Cuidong; Burkhardt, Tania; Rossi, Michael R; LaDuca, Jeffrey; Matsui, Sei-Ichi; Vaughan, Mary; Hicks, David G; Heintz, Nathaniel; Cowell, John K (Mammalian genome, 2007)
The LGI1 gene has been implicated in the development of epilepsy and the invasion phenotype of glial cells. Controversy over the specific tissue expression pattern of this gene has stemmed from conflicting reports generated using immunohistochemistry and the polymerase chain reaction. LGI1 is one of a four-member family of secreted proteins with high homology and here we demonstrate, using GFP-tagged constructs from the four LGI1family members, that commonly used antibodies against LGI1 cross-react with different family members. With the uncertainty surrounding the use of commercially available antibodies to truly establish the expression pattern of LGI1, we generated transgenic mice carrying the LGI1-containing BAC, RP23-127G7, which had been modified to express the GFP reporter gene under the control of the endogenous regulatory elements required for LGI1 expression. Three founder mice were generated, and immunohistochemistry was used to determine the tissue-specific pattern of expression. In the brain, distinct regions of glial and neuronal cell expression were identified, as well as the choriod plexus, which is largely pia-derived. In addition, strong expression levels were identified in glandular regions of the prostate, individual tubules in the kidney, sympathetic ganglia in the kidney, sebaceous glands in the skin, the islets of Langerhans, the endometrium, and the ovary and testes. All other major organs analyzed were negative. The pattern of reporter gene expression was identical in three individual founder mice, arguing against a position effect altering expression profile due to the integration site of the BAC.